DynaMoVis: Visualization of dynamic models for urban modeling - Joel Dearden (The Visual Computer, 2015)
In association with Urban modelers, we have created DynaMoVis, a system for the visualization of dynamic models. The prediction of the evolution of urban and ecological systems is difficult because they are complex nonlinear systems that exhibit self-organization, emergence and path dependence. Without a good understanding of the dynamics, interventions might have unintended side-effects. This study aims to make progress in the understanding of dynamic models in the application areas of urban modelling. Analyzing these simulations is challenging due to the large amount of data generated and the high-dimensional nature of the system. We present a visualization system for exploring the behavior of a simulation from many different points of view. The system contains a number of different modes which allow exploration of: the simulation parameter space, the introduction and effect of noise on the simulation and the basins of attraction in the phase space of the simulation. Through use of this system it has been possible to develop a deeper understanding of the inter-dependencies in the models, their parameter spaces and corresponding phase spaces.